BIOECOLOGICAL SAFFLOWER CHARACTERISTICS (CARTHAMUS TINCTORIUS L.) PLANT - Eshchanova Sh.M., Tursunboev H.E., (EPRA International Journal of Research and Development (IJRD), 2023)
The article contains information about the beneficial properties of the Safflower (Carthamus tinctorius L.) plant and its cultivation in the conditions of Karakalpakstan..